OPTIMALISASI JARINGAN NIRKABEL DENGAN METODE RSSI DI AIKOM TERNATE - Laroma Larumbia; Susanti H Hasan; Seh Turuy (Universitas Nusa Cendana, 2021)
TThis study aims to optimize the wireless network from blind spots in the AIKOM Ternate environment. These blind spot areas make wireless network users (lecturers, staff, and students) uncomfortable because they have to get close to the nearest network source (access point (AP)) in order to access the internet or intranet network. With this wireless network optimization, the coverage area of ​​the wireless network is adjusted according to the need so that there are no more blind spots. The use of the Wireless Monitoring (Wirelessmon) application to detect the coverage area of ​​each installed AP, which is measured is the receive signal strength indicator (RSSI), including the determination of channel usage from each AP so as not to overlap in channel usage on each AP and the data rate that is experiencing increase and decrease according to the quality of the received signal. The results of this study indicate that after the optimization was carried out by installing the AP at five points. Optimization of the wireless network at the AIKOM Ternate campus was successful with RSSI -61dBm to -44dBm, RSSI was included in the very good category. It is recommended that RSSI measurements use more than one software so that comparisons are carried out, make comparisons of the received RSSI with the resulting throughput on different devices, and network administrators can use the results of this study but the use of devices with specifications that are different from those used in this study is suggested to perform retrieval of data so that the results are maximum.